Strategic inequality: social status in French criminal interrogations, 1750-1850 - Hofman, Elwin (Crime, histoire & sociétés, 2022)
Criminal procedure in eighteenth-century France is regularly seen as unequal. This article engages with this view by attending to the role of social status during criminal interrogations in the final decades of the old regime and the first of the new. It argues that, throughout this period, in sources such as laws, doctrines, reformist critiques and interrogation transcripts, a general concern for equality, especially wealth equality, is discernible. However, magistrates did sometimes adapt their interrogation strategies to the social status of the suspect. This did not always mean that they treated suspects of a higher social status more leniently. Rather, they strategically adapted their techniques in order to interrogate more successfully.